A revision of Lestidae Calvert, 1901 (Odonata: Zygoptera) from Colombia, with the first record of Lestes dichrostigma Calvert, 1909 - Mendoza-Penagos, Cristian Camilo; Pérez-Gutiérrez, León A.; Muzón, Javier (Zootaxa, 2024)
The cosmopolitan family Lestidae Calvert, 1901 has two widely distributed genera in the Americas: Archilestes Selys, 1862, and Lestes Leach, 1815. In Colombia, this family is represented by 11 species. In this study, we present a diagnosis of Lestidae species in Colombia based on a thorough review of the country’s main entomological collections. A total of 258 specimens representing ten species were examined. The species L. dichrostigma Calvert, 1909, is recorded for the first time. The presence of L. henshawi Calvert, 1907 is excluded, and the taxonomic status of L. sternalis (Navás, 1930) is discussed. Finally, we present distribution maps, photographs of Lestidae species, taxonomical important structures, and taxonomic keys for both males and females.